The Mennonite encyclopedia ; Vol. 1. A-C a comprehensive reference work on the Anabaptist-Mennonite movement - Dyck, Cornelius J.; Martin, Dennis D., 1952- (USA Mennonite Publishing House, 1976)
Comprehensive reference work covering 400 years of the history, faith, life, culture of Anabaptism-Mennonitism
Keywords: Dogmatic Theology (3GddGghJ GdYbjOjs; Mennonites -- Encyclopedias; Anabaptists -- Encyclopedias